Tawaran Model Kurikulum Islamic Integrated Character - Irfan Kuncoro (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
This article discusses the Islamic Integrated Character curriculum model which is a formula for the needs of today's institutions. This article uses a qualitative descriptive analysis of the object of discussion by utilizing reference sources on related themes. This article argues that the Islamic Integrated Character curriculum model is an ideal curriculum to be applied, this is because it is in accordance with the current needs of the nation, where this model is integrated between the curriculum and Islamic Character which in the end is not limited to general knowledge and to help eliminate the dichotomy between the general education system and Islam, so that understanding/learning will provide comprehensive student learning outcomes and be able to print the Ulul Albab generation. By applying the Islamic Integrated Character curriculum model, students will be able to recognize, understand, reflect, have faith, fear, and have noble character in carrying out the teachings correctly. Furthermore, the Islamic Integrated Character Curriculum has a positive effect on increasing higher-order thinking skills and improving the character of students compared to students using conventional methods, it can be said to be effective in improving students' higher-order thinking skills, so that it will produce a generation of Insan Kamil.